Phytoremediation of metals by colonizing plants developed in point bars in the channeled bed of the Dilúvio Stream, Southern Brazil. Issue 1 (2nd January 2022) - Maggioni dos Santos, Vinícius; Capeleto de Andrade, Leonardo; Tiecher, Tales; Andreazza, Robson; Camargo, Flávio Anastácio de Oliveira
Abstract: Urban rivers are intensely impacted by pollution with metals resulting from anthropogenic activities, and these elements present in water and sediments can be ecofriendly phytoremediated. This study aimed to evaluate the levels of metals in the sediments and colonizing plants growing in point bars in the channeled bed of the Dilúvio Stream, Southern Brazil. Sediment and plants were sampled at five-point bars with consolidated vegetation. These point bars are formed mainly by sand, with increasing concentrations of clay plus silt, carbon, nitrogen, and metals (Zn, Cu, Cr, Ni, Pb, and Cd) downstream. The concentration of Zn (338 μg/g) and Cu (219 μg/g) in sediments were 1.6 and 1.11 above the probable effect level at the most downstream site. The translocation factor was low in all sites and for all potentially toxic metals evaluated (ranging from 0.01 to 0.63). However, bioaccumulation factor exhibited high values, especially for Cd (average of 2.51), Ni (1.62), Zn (1.49), and Cr (1.25), suggesting that the colonizing plants have more potential for phytostabilization and phytoaccumulation than phytoextraction. These plants can be considered as natural filtering reducing the environmental contamination and the flow of these contaminants in the drainage network. Statement of novelty: Colonizing plants growing in point bars of urban rivers are common around the world; however, their phytoremediation potential is poorly studied. Colonizing plants may be useful for phytoremediation of water, effluents, and sediments of the Dilúvio Stream (Southern Brazil), polluted by potentially toxic metals that originated from the urbanization.